A Randomized Clinical Trial of Atomoxetine for Mild Cognitive Impairment in Parkinson's Disease. Issue 3 (17th November 2016) - Hinson, Vanessa K.; Delambo, Amy; Elm, Jordan; Turner, Travis
Abstract: Background: Mild cognitive impairment in Parkinson's disease (PD‐MCI) is associated with diminished norepinephrine from the locus coeruleus to the prefrontal cortex. Atomoxetine is a specific norepinephrine reuptake inhibitor that has been approved by the US Food and Drug Administration to treat attention deficit hyperactivity disorder in adults. The authors hypothesized that atomoxetine would improve attention and executive functioning in patients with PD‐MCI. Methods: Thirty participants who met Movement Disorder Society Task Force Level I criteria for PD‐MCI were enrolled in a randomized controlled trial of atomoxetine. Cognitive evaluations were performed at baseline and after 10 weeks of treatment or placebo. A safety visit was performed at Week 12. A global statistical test was used to examine treatment effects on standardized tests of attention, working memory, processing speed, and set shifting (primary outcome measure). Secondary outcomes included cognitive measures hypothesized to be insensitive to atomoxetine, the Conners Adult Attention Deficit Hyperactivity Disorder Rating Scale, and safety measures. Results: Fifteen participants were randomized to each arm. Groups were similar on medical and demographic variables and baseline cognition. Three serious adverse events occurred; 2 on atomoxetine (syncope, isolated episode of atrial fibrillation) and 1 on placebo (atrial fibrillation). The global statistical test of primary outcome measures did not reveal a significant difference between groups. However, significant improvements were observed for atomoxetine but not placebo on subjective measures of attention and impulsivity (Conners Adult Attention Deficit Hyperactivity Disorder Rating Scale). Conclusions: Atomoxetine treatment produced subjective, but not objective, improvements in PD‐MCI. Failure to detect objective differences may be due to insensitivity of cognitive tests or severity of cognitive deficits in the study participants.